The Long-term Effects of School Quality on Labor Market Outcomes and Educational Attainment - Christian Dustmann; Patrick A. Puhani; Uta Schönberg (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2012)
We study the long-term causal effects of attending a "better" school - defined as one with more advanced peers, more highly paid teachers, and a more academic curriculum - on the highest degree completed, wages, occupational choice, and unemployment. We base our analysis on a regression discontinuity design, generated by a school entry age rule, that assigns students to different types of schools based on their date of birth. We find that, even though our case involves larger inter-school differences in peer quality and teaching curricula than in most previous studies, the long-term effect of school quality is very small and not significantly different from zero. This surprising finding is partly explainable by the substantial amount of student up- and downgrading between schools of varying quality at the end of middle school (age 15/16) and at the end of high school (age 18/19). This suggests that giving people a "second chance" during their education can make up for several years of schooling with a less challenging peer group and a less challenging teaching curriculum.
Keywords: I21; J10; 330; School quality; peer effects; regression discontinuity design